2005
DOI: 10.18267/j.pep.261
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Monetary Policy on Economic Instability in Turkey (1983 - 2003)

Abstract: Abstract:This article aims at revealing the effectiveness of Turkish monetary policy in controlling inflation rate and the stability of exchange rate using the rational expectation framework that incorporates the fiscal role of exchange rate. Based on quarterly data covering the period between 1983: Q4 and 2003: Q4, the analysis affirms that the effort of the Turkish monetary policy at influencing the finance of government fiscal deficit through the determination of the inflation-tax rate, to some extent, affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The empirical result revealed that monetary stock (M2), which is money supply, is an effective tool to influence and control the monetary assets in Pakistan. (Ferdiun, 2005), who studied the impact of monetary policy on economic instability in Turkey, confirmed that monetary policy effectiveness in Turkey's economic manages and controls over inflation and exchange rate stability. (Hameed, 2010) who also studies the impact of monetary policy on economic growth has indicated that money supply, inflation and interest rate played a major significant role on GDP growth in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 86%
“…The empirical result revealed that monetary stock (M2), which is money supply, is an effective tool to influence and control the monetary assets in Pakistan. (Ferdiun, 2005), who studied the impact of monetary policy on economic instability in Turkey, confirmed that monetary policy effectiveness in Turkey's economic manages and controls over inflation and exchange rate stability. (Hameed, 2010) who also studies the impact of monetary policy on economic growth has indicated that money supply, inflation and interest rate played a major significant role on GDP growth in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 86%
“…There is no consensus among the experts on whether military spending affects debt, but scholars who agree that it does have an impact are in a majority (Brzoska, 1983;Dunne et al, 2004a;Narayan and Smyth, 2008;Shahbaz et al, 2011;Zhang et al, 2016). Some scholars deny that military spending affects debt (Sezgin, 2004) or believe it has no impact (Gülay and Sezgin, 2002;Feridun, 2005). Considering that six financial crises in the 1990s…”
Section: Introductionmentioning
confidence: 99%